The Implementation of Henon Map Algorithm for Digital Image Encryption - Edi Sukirman; Suryadi MT; M. Agus Mubarak (Universitas Ahmad Dahlan, 2014)
Security information is a very important aspect that must be noticed. Information not only in the form of text but also in form of data image. Using data encription to send private information have been widely use. But still need to improve the endurance from bruto force attack. One ways to improve it, is by using chaos theory with henom algorithm. Test result gave the alghoritm can encrypt image data from grayscale type to colorfull type. Encryption and descryption time proportional to the size image. Composition and variety coulor doesn’t effect the time. This algorithm has key space of and key sensitivity up to . So, it can be concluded that, the algorithm is very difficult to be cracked by brute force attack.